2023
DOI: 10.3390/ani13111722
|View full text |Cite
|
Sign up to set email alerts
|

Lameness in Pregnant Sows Alters Placental Stress Response

Abstract: Pregnant sows from commercial pig farms may experience painful states, such as lameness, an essential indicator in assessing sow welfare. We investigated the effect of lameness during the last third of pregnancy on reproductive performance and placental glucocorticoid concentrations in sows. Periodic locomotion assessments were carried out on two commercial pig farms using a validated 0–5 scoring system (from 0: normal locomotion; to 5: a downer animal). Sows from both farms (N = 511) were grouped based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Lesions in the locomotor system can be related to lameness 7 . The prevalence of lameness in sows is rarely reported and is usually underestimated, with reports ranging from 8 to 65% 8 10 . In a study by Jorgensen 7 , lesions were identified in the locomotor systems of 71–99% of the sows, including surface lesions on the claw and heel, as well as inappropriate claw sizes and excessive wear on the sidewall of the claw.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions in the locomotor system can be related to lameness 7 . The prevalence of lameness in sows is rarely reported and is usually underestimated, with reports ranging from 8 to 65% 8 10 . In a study by Jorgensen 7 , lesions were identified in the locomotor systems of 71–99% of the sows, including surface lesions on the claw and heel, as well as inappropriate claw sizes and excessive wear on the sidewall of the claw.…”
Section: Introductionmentioning
confidence: 99%
“…Lameness often goes unnoticed in its early stages; as a result, the animals receive treatment at advanced ages 2 . It is of outmost importance to carry out a diagnosis of lameness in the early stages of the condition in order to prevent situations of stress and unnecessary pain for the animal 8 and to promote quick recovery. Identifying sows with early signs of lameness is ideal for improving welfare and reducing economic impacts 2 , 19 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of lameness in sows is rarely reported and is usually underestimated, with reports ranging from 8-65% [7] [9] [10]. In a study by Jorgensen [7], lesions were identi ed in the locomotor systems of 71-99% of the sows, including surface lesions on the claw and heel, as well as inappropriate claw sizes and excessive wear on the sidewall of the claw. In another study, it was found that 96% of sows had cracks in the heel [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lameness is exhibit throughout the breeding cycle of the pig and can be diagnosed in the rst three weeks of the piglet's life [6]. Lesions in the locomotor system can be related to lameness [7]. The prevalence of lameness in sows is rarely reported and is usually underestimated, with reports ranging from 8-65% [7] [9] [10].…”
Section: Introductionmentioning
confidence: 99%